1989
DOI: 10.1029/gl016i008p00903
|View full text |Cite
|
Sign up to set email alerts
|

Slow shock characteristics as a function of distance from the X‐line in the magnetotail

Abstract: Both particle and MHD simulations are performed to study the characteristics of slow shocks in the magnetotail. The particle simulations indicate that switch-off shocks exhibit large amplitude rotational wave trains, while magnetotail slow shocks with an intermediate Mach number MA• < M,: _• 0.98 do not display such rotational wave trains. The MHD simulations show that the spontaneous reconnection process in the near-earth plasma sheet leads to the formation of a pair of slow shocks tailward of the reconnectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 23 publications
1
28
1
Order By: Relevance
“…A series of MHD discontinuities can be generated by magnetic reconnection. [2][3][4][5][6] Observations of slow shocks in the solar wind have been reported by Chao and Olbert, 7 Feldman et al, 8 and Saito et al 9 In hybrid simulations of slow shock, leakage of downstream heated ions to the upstream leads to an anisotropy pressure in the foreshock region, [10][11][12][13][14] in which the local intermediate-mode speed is highly reduced. Rotational discontinuities have been observed in the solar wind.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…A series of MHD discontinuities can be generated by magnetic reconnection. [2][3][4][5][6] Observations of slow shocks in the solar wind have been reported by Chao and Olbert, 7 Feldman et al, 8 and Saito et al 9 In hybrid simulations of slow shock, leakage of downstream heated ions to the upstream leads to an anisotropy pressure in the foreshock region, [10][11][12][13][14] in which the local intermediate-mode speed is highly reduced. Rotational discontinuities have been observed in the solar wind.…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies have also shown that the tail lobe-plasma sheet boundary in the mid-and distant tail often behaves as a quasi-perpendicular slow shock, which may be due to the Petschek-type reconnection occurring in the tail. 8,9,12,14,[24][25][26][27][28][29][30][31][32][33] However, with a statistical survey from Geotail and Wind data, Whang et al 22 argued that occurrence of DDs in the tail lobe-plasma sheet boundary is no less than the stand-along slow shocks, which implies that the DDs are easy to be generated in the geomagnetic tail.…”
Section: Introductionmentioning
confidence: 96%
“…However, observations in the geomagnetic tail (on board the ISEE-3 rocket) failed to detect the presence of such waves. To eliminate the inconsistency between theoretical predictions and observations, researchers have conducted a multitude of calculations using hybrid models [70][71][72][73][74][75][76]. These studies have obtained shocktype solutions both with and without a wave chain.…”
Section: Slow Shocksmentioning
confidence: 97%
“…These studies have obtained shocktype solutions both with and without a wave chain. According to [70,73], there is a critical Mach number Me = 0.98 such that for SS with 1 > M~ > Mc the downstream region contains a coherent wave chain, while for SS with MI < Me the rotational wave in the downstream region decays over a distance shorter than the wavelength. (For the magnetic tail SS with 0Bn= 75 ~ [~ 1 = 0.1, and Tel / Til = 0, the critical value is Me = 0.975 [73].)…”
Section: Slow Shocksmentioning
confidence: 99%
“…The two distances for the first plasmoid are consistent with the mid-tail and distant X-lines, and for the second plasmoid with the near-Earth and distant X-lines. However the size of the plasmoid in X may be less than the distance between the two X-lines, because a plasmoid is a plasma bulge and the bulge does not necessarily start from the position of the X-line: there can be a thin plasma sheet region between the X-line and the bulge (e.g., Lee et al, 1989). Also, the spacecraft may not encounter the full length of the plasmoid, leading to an underestimation of the plasmoid length.…”
Section: Discussionmentioning
confidence: 99%